Identity-based anonymity authentication protocol in the heterogeneous wireless network - HOU Hui-fang1; JI Xin-sheng2; LIU Guang-qiang1 (Tongxin xuebao)
Aiming at the security of authentication protocol for heterogeneous wireless network,a mutual authentication and key agreement protocol,which was based on CPK algorithm and improved ECDH algorithm,was proposed.The temporary authentication identity and temporary communication identity was adopted to realize user identity anonymity.The ordered pair of temporary communication identity was proposed to prevent replay attack in the process of re-authentication.The risk of key compromise was also avoided in the proposed protocol.By security analysis,this protocol had the security properties such as identity authentication,key security and anonymity.